2015
DOI: 10.1002/dys.1516
|View full text |Cite
|
Sign up to set email alerts
|

Verbal Short‐Term Memory Deficits in Chinese Children with Dyslexia may not be a Problem with the Activation of Phonological Representations

Abstract: This study explored the underlying mechanism of the verbal short-term memory deficit in Chinese children with developmental dyslexia. Twenty-four children with dyslexia and 28 age-matched normal readers participated in the study. They were required to memorize a visually presented series of six Chinese characters and identify them from a list also including code-specific distracters and non-code-specific distracters. Error rates were recorded and were higher for code-specific distracters in all three condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 77 publications
1
7
0
1
Order By: Relevance
“…Boets et al (2013) also postulated that the phonetic representation in individuals with dyslexia was intact, the phonological processing deficit in dyslexia lay in the inefficient accessing process which was underpinned by the white fiber connections between Broca's region and Werniche's region. Even further, Zhao, Yang, Song, and Bi (2015) recently reported that children with dyslexia could activate phonological representations sufficiently in a verbal short-term memory task. If in this case that phonological representation is intact and is activated sufficiently, the impairment in exact addition resulting from verbal/phonological deficit probably resides in the processing and utilization of those intact phonetic representations.…”
Section: Discussionmentioning
confidence: 97%
“…Boets et al (2013) also postulated that the phonetic representation in individuals with dyslexia was intact, the phonological processing deficit in dyslexia lay in the inefficient accessing process which was underpinned by the white fiber connections between Broca's region and Werniche's region. Even further, Zhao, Yang, Song, and Bi (2015) recently reported that children with dyslexia could activate phonological representations sufficiently in a verbal short-term memory task. If in this case that phonological representation is intact and is activated sufficiently, the impairment in exact addition resulting from verbal/phonological deficit probably resides in the processing and utilization of those intact phonetic representations.…”
Section: Discussionmentioning
confidence: 97%
“…In a recent study, Chinese dyslexics showed reduced short-term verbal memory during recall of Chinese characters than age-matched normal readers. 31 Given reported implication of CREBBP in memory impairment as well as developmental and intellectual abnormalities, understanding functional effects of rs8049367 on CREBBP in future studies might explain its contribution to DD.…”
Section: Discussionmentioning
confidence: 99%
“…It is obvious that, raw scores of the test are measured based on the standard difficulty coefficient. And many previous studies with Chinese dyslexia used the raw scores of this vocabulary test to select dyslexia children ( Shu et al, 2006 ; Meng et al, 2007 ; Wang et al, 2010 ; Yang and Hong-Yan, 2011 ; Liu et al, 2012 , 2013 ; Yang et al, 2013 ; Qian and Bi, 2014 ; Zhao et al, 2014 , 2015 ). Besides, in this current study, the inclusionary criterion for dyslexics was their written score at least 1.5 standard deviation ( SD ) below the average score of all participants, not a fixed score.…”
Section: Methodsmentioning
confidence: 99%